Assessment of sexual dysfunction in patients with inflammatory bowel disease - Dorota Szydlarska; Alicja Jakubowska; Grażyna Rydzewska (Gastroenterology Review)
Inflammatory bowel disease (IBD) represents a diverse variety of chronic inflammatory intestinal conditions. Sexuality is often disturbed in patients with IBD, more often affecting women than men. Many factors seem to contribute to intimacy concerns. The most popular questionnaires used in empirical research around the world are the Female Sexual Function Index (FSFI) for women and the International Index of Erectile Function (IIEF) for men. Sexual satisfaction was negatively correlated with depression, anxiety, sexual problems, and illness perceptions. When analysing the problem of IBD, disorders of sexual function should not be ignored. Patients should be screened for psychological diseases and sexual dysfunction, and necessary treatments should be given as soon as possible. By understanding what factors contribute to poor sexual functioning in patients with IBD, we may try to minimise adverse psychosocial events. Screening for sexual disorders should be a part of daily medical practice.